The implementation of Internet Protocol Virtual Private Network (IPVPN) in Telekom Malaysia / Azlinda Hameed Sultan - Hameed Sultan, Azlinda (2004)
The Internet has changed and will continue to change the way businesses operate. The rise of Internet as a business platform has resulted enterprises seek to leverage the benefits of Internet-based solution, and the industry has seen the establishment and increasing acceptance of Internet Protocol Virtual Private Network or in short IPVPN. Typically, IPVPN uses the Internet as the transport backbone to establish secure links with business partners, extend communications to regional and isolated offices and significantly decrease the cost of communications for an increasingly mobile workforce. As a result of that, Telekom Malaysia as the leading telecommunication company in Malaysia has taken forward step in implementing IPVPN as its aims in providing world class services to its customers. The scope of this study concentrates on the analysis of the implementation of Global Internet Protocol Virtual Private Network in Telekom Malaysia perspective. Various important information on the definition, distinguish between Virtual Private Network (VPN) and IPVPN, the technology architecture that is available in the market today and benefits to enterprise and service providers of IPVPN were gathered and discussed in the literature review. Furthermore the two main challenges associated with the implementation of IPVPN which is the security aspect and the Quality of Service (QoS) were focused in depth.